Economic and Financial Feasibility Analysis: Small Hydroelectric Power Plant at the São Bento River Dam - Castro, João Paulo Sartor; Machado, Tamiris; Nunes, Carina; Fabris, Thiago Rocha; Picolo, Jaime; Watanabe, Melissa (International Journal of Advanced Engineering Research and Science, 2022)
Small Hydroelectric Power Plants (SHP) are hydroelectric plants that are part of the Brazilian energy matrix and have a low environmental impact. The present work aims to analyze the economic and financial feasibility for the implementation of a Small Hydroelectric Power Plant, in the São Bento River dam, located in the municipality of Siderópolis, state of Santa Catarina. As a methodology, the research is classified as exploratory and uses a case study. As for data analysis, a quantitative approach was adopted, since it is a feasibility study of a project, which involves analysis of data referring to costs, operating profit and expenses. Investments, income and expenses were analyzed, and this made it possible to prepare income statements, cash flows and economic indicators, as a way of analyzing the feasibility of the enterprise. The results were positive, indicating the feasibility of the project, through the analysis of minimum attractiveness rate, net present value and payback.